2021
DOI: 10.11594/jk-risk.01.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Efektifitas Neuromuscular Taping (NMT) sebagai Terapi Non-Farmakologi pada Penderita Carpal Tunnel Syndrome di RS Saiful Anwar, Malang: Sebuah Laporan Kasus

Abstract: Pendahuluan: Carpal Tunnel Syndrome (CTS) adalah lesi saraf tepi yang sering ditemui karena mekanisme non-trauma. Metode terapi CTS bermacam-macam yang tujuannya untuk mengurangi keluhan dan meningkatkan produktivitas pasien. Salah satu metode non-farmakologi yang bisa digunakan adalah dengan Neuromuscular Tapping (NMT). Tujuan dari laporan kasus ini adalah untuk mengetahui efektivitas penggunaan NMT sebagai terapi non-farmakologi pada pasien CTS yang sebelumnya telah mendapatkan terapi farmakologis, diukur de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Neuromuscular taping provides a stimulus to the afferent nerves to enlarge the intestinal space with folds for a decompressive effect. The study by Eparla, et al compared the results between taping and steroid injection in elbow epicondylitis, it was found that steroid injection, taping, and medication were effective in reducing pain, and functional scores at the end of the 2nd week and the only treatment that continued to be effective until week 4 is the taping group (Setianto et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Neuromuscular taping provides a stimulus to the afferent nerves to enlarge the intestinal space with folds for a decompressive effect. The study by Eparla, et al compared the results between taping and steroid injection in elbow epicondylitis, it was found that steroid injection, taping, and medication were effective in reducing pain, and functional scores at the end of the 2nd week and the only treatment that continued to be effective until week 4 is the taping group (Setianto et al, 2021).…”
Section: Introductionmentioning
confidence: 99%